2017
DOI: 10.7860/jcdr/2017/29300.10605
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid in Chronic Obstructive Pulmonary Disease: A Hospital Based Case Control Study

Abstract: Serum uric acid is a simple, cost effective biochemical test which may be useful in risk stratification of subjects with newly diagnosed chronic obstructive pulmonary disease. Hyperuricaemia is associated with advance duration and stage of COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…A total of 20 articles were retrieved for full-length article review and 12 articles were excluded at this stage as they did not report the level of serum uric acid among participants with and without COPD. Finally, eight studies [12][13][14][15][16][17][18][19] with 1,612 participants were eligible for the meta-analysis. The literature retrieval, review and selection process are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 20 articles were retrieved for full-length article review and 12 articles were excluded at this stage as they did not report the level of serum uric acid among participants with and without COPD. Finally, eight studies [12][13][14][15][16][17][18][19] with 1,612 participants were eligible for the meta-analysis. The literature retrieval, review and selection process are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The increased level of serum uric acid is thought www.journals.viamedica.pl to be a consequence of increased purine catabolism in the presence of tissue hypoxia [11]. The current systematic review and meta-analysis was conducted to compare serum uric acid level between patients with COPD, a common hypoxemic disorder, and individuals without COPD [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation given was that hypoxia in subjects with impaired pulmonary function can induce the production of uric acid. 11 Subjects with milder COPD (stages 1 and 2) were having lower uric acid than stages 3 and 4. An study from Egyptian journal of bronchology (EJB) showed median range of uric acid for severe and very severe disease as 7.6 mg/dL and 7.9 mg/dL respectively.…”
Section: Discussionmentioning
confidence: 95%
“…In the similar study, Rajlaxmi et al, also revealed that nonsmokers had higher (p>0.05) uric acid level than smokers but contrary to their study, results were statistically significant (p <0.05). 11 This finding possibly suggests that smoking reduces the antioxidant property of uric acid in the upper airways leading to increase risk and/or severity of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricaemia has been implicated in the pathogenesis of several human diseases with systemic inflammation; notably gout, vascular diseases such as atherosclerosis, hypertension, metabolic syndrome, as well as in various malignancies such as cancer of lungs, hematological malignancies, etc., [10]. Importantly, serum uric acid has been proposed as a marker for impaired oxidative metabolism & systemic inflammation and an independent predictor of impaired prognosis in several processes such as congestive heart failure primary pulmonary hypertension & acute myocardial infarction [11].…”
Section: Introductionmentioning
confidence: 99%